Did the Harappan settlement of Dholavira (India) collapse during the onset of Meghalayan stage drought?. (26th December 2019) - Sengupta, Torsa; Deshpande Mukherjee, Arati; Bhushan, Ravi; Ram, F.; Bera, M. K.; Raj, Harsh; Dabhi, Ankur J.; Bisht, R. S.; Rawat, Y. S.; Bhattacharya, S. K.; Juyal, Navin; Sarkar, Anindya
ABSTRACT: Radiocarbon dating of archaeological carbonates from seven cultural stages of Dholavira, Great Rann of Kachchh (GRK), the largest excavated Harappan settlement in India, suggests the beginning of occupation at 5500 years BP (pre‐Harappan), and continuation until 3800 years BP (early part of the Late Harappan period). The settlement rapidly expanded under favourable monsoonal climate conditions when architectural elements such as the Citadel, Bailey, Lower and Middle Town were added between the Early and mid‐Mature Harappan periods. Abundant local mangroves grew around the GRK sustaining prolific populations of the edible gastropod Terebralia palustris . Oxygen isotope (δ 18 O) sclerochronology of Early Harappan gastropod shell suggests seasonal mixing of some depleted (δ 18 O −12‰) river water in summer/monsoon months (through ancient Saraswati and/or Indus distributary channels) with seawater that periodically inundated the GRK. Evaporation from this semi‐enclosed water body during the non‐monsoon months enriched the δ 18 O of water/shell carbonates. The humid fluvial landscape possibly changed due to a catastrophic drought driving the final collapse of the settlement of Dholavira exactly at the onset of the Meghalayan (Late Holocene) stage ( 4300–4100 years BP ). Indeed, Dholavira presents a classic case for understanding how climate change can increase future drought risk as predicted by the IPCC working group. Copyright © 2019 John Wiley & Sons, Ltd.